Gender-Just Reparations: Key Elements and Approaches. - McEvoy, Bretton James. (Tufts Archival Research Center, 2014)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: For far too long, civilian non-combatants have borne the violent consequences of armed conflict and political repression. With the modern propensity for “wars amongst the people,” that trend has only continued, as civilian populations are repeatedly embroiled within – if not the direct targets of – violence and terror. And yet, despite profound experiences of harm, the suffering of victim-survivors – and of women and girls in particular – is all-too-often forgotten or rendered inconsequential in the period’s aftermath, with priority typically directed at broader reconciliation, development and institutional reform initiatives. My thesis seeks to contribute to a reformulation of this imbalance, shifting greater emphasis onto the repair of female victim-survivors – as their legal right, their due recognition, and an essential starting point in (re)building a peaceful society that values women and girls as equal citizens and rights holders. To that end, I outline key elements and methodological approaches of a gender-just reparations program – illuminated by recent successes and failures – striving for both conceptual depth as well as practical guidance in the design and implementation of reparations programming.